Mimicking behaviors in separated domains (abstract reprint) - De Giacomo, G; Fried, D; Patrizi, F; Zhu, S (Association for the Advancement of Artificial Intelligence, 2024)
This is an abstract reprint of a journal article by Giacomo, Fried, Patrizi, and Zhu (2023).